2020
DOI: 10.1042/cs20190728
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle redox signaling in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by synovitis and the presence of serum autoantibodies. In addition, skeletal muscle weakness is a common comorbidity that contributes to inability to work and reduced quality of life. Loss in muscle mass cannot alone account for the muscle weakness induced by RA, but instead intramuscular dysfunction appears as a critical factor underlying the decreased force generating capacity for patients afflicted by arthritis. Oxidative stress and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 130 publications
(233 reference statements)
0
14
0
1
Order By: Relevance
“…Our data showed that after short period hypoxia induction, the expression level of HIF-1a in Claudin-5 112Δ5 and Claudin-5 297Δ4 mutant bEnd.3 cells was significantly lower than that in Claudin-5 wt bEnd.3 cells. As a downstream effecter of iNOS, ROS is usually produced by various sources in the CNS, including mitochondria, NADPH oxidase, and NOS ( Galley, 2011 ; Chan and Chan, 2014 ; Steinz et al, 2020 ). We used DCFH-DA to measure the ROS level in endothelial cells, and the data showed that the ROS generation in Claudin-5 wt bEnd.3 cells were higher than those in Claudin-5 112Δ5 and Claudin-5 297Δ4 bEnd.3 cells in response to early hypoxia stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that after short period hypoxia induction, the expression level of HIF-1a in Claudin-5 112Δ5 and Claudin-5 297Δ4 mutant bEnd.3 cells was significantly lower than that in Claudin-5 wt bEnd.3 cells. As a downstream effecter of iNOS, ROS is usually produced by various sources in the CNS, including mitochondria, NADPH oxidase, and NOS ( Galley, 2011 ; Chan and Chan, 2014 ; Steinz et al, 2020 ). We used DCFH-DA to measure the ROS level in endothelial cells, and the data showed that the ROS generation in Claudin-5 wt bEnd.3 cells were higher than those in Claudin-5 112Δ5 and Claudin-5 297Δ4 bEnd.3 cells in response to early hypoxia stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle contains three NOS subtypes, which are neuronal NOS (nNOS), inducible NOS (iNOS) and endothelial NOS (eNOS) ( Hussain et al, 1985 ; Ohkoshi et al, 1997 ; Tengan et al, 2012 ). NOS enzymes are also regards as a origin of O 2 •- production that occurs when NOS is uncoupled from its substrate L-Arg and its cofactor BH 4 ( Luo et al, 2014 ; Steinz et al, 2020 ). NO • is a radical because it contains one unpaired electron on the antibonding ( Valko et al, 2007 ).…”
Section: Reactive Oxygen/nitrogen Species and Antioxidants In Skeleta...mentioning
confidence: 99%
“…Systemic activation of pro-inflammatory molecules can potentially contribute to muscle fibre proteolysis and decrease protein synthesis [ 9 ]. Muscle injury has been regarded as an important contributor to RA-induced morbidity and mortality [ 13 ]. Bone and joint manifestations have a broad spectrum in COVID-19 with common viral arthralgia [ 14 ].…”
Section: Covid-19 and Ra Associationmentioning
confidence: 99%